Early identification of ADHD risk via infant temperament and emotion regulation: a pilot study. (12th May 2015) - Sullivan, Elinor L.; Holton, Kathleen F.; Nousen, Elizabeth K.; Barling, Ashley N.; Sullivan, Ceri A.; Propper, Cathi B.; Nigg, Joel T.
<x xml:space="preserve">Abstract</x> Background Attention deficit hyperactivity disorder (ADHD) is theorized to have temperamental precursors early in life. These are difficult to identify because many core features of ADHD, such as breakdowns in executive function and self‐control, involve psychological and neural systems that are too immature to reliably show dysfunction in early life. ADHD also involves emotional dysregulation, and these temperamental features appear earlier as well. Here, we report a first attempt to utilize indices of emotional regulation to identify ADHD‐related liability in infancy. Methods Fifty women were recruited in the 2nd trimester of pregnancy, with overselection for high parental ADHD symptoms. Measures of maternal body mass index, nutrition, substance use, stress, and mood were examined during pregnancy as potential confounds. Offspring were evaluated at 6 months of age using LABTAB procedures designed to elicit fear, anger, and regulatory behavior. Mothers completed the Infant Behavior Questionnaire about their child's temperament. Results After control for associated covariates, including maternal depression and prenatal stress, family history of ADHD was associated with measures of anger/irritability, including infant negative vocalizations during the arm restraint task (p = .004), and maternal ratings of infant distress to limitations (p = .036). In the regulation domain, familial ADHD was associated with less parent‐oriented attention seeking during the still face procedure (p < .001), but this was not echoed in the maternal ratings of recovery from distress. Conclusions Affective response at 6 months of age may identify infants with familial history of ADHD, providing an early indicator of ADHD liability. These preliminary results provide a foundation for further studies and will be amplified by enlarging this cohort and following participants longitudinally to evaluate ADHD outcomes.